CULTURAL DIFFERENCES AFFECTING ENGLISH-KARAKALPAK TRANSLATION - Usakhov Rustem Muratovich (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the significant impact of cultural differences on the translation process between English and Karakalpak. Given the increasing importance of cross-cultural communication in a globalized world, understanding how cultural nuances influence translation is crucial for achieving accurate and meaningful interpretations. Through a qualitative analysis of various literary texts, this research identifies key cultural disparities, including linguistic variations, social norms, and historical contexts that shape the translation landscape. The findings reveal that translators often encounter challenges related to idiomatic expressions, contextual meanings, and cultural references that do not have direct equivalents in the target language.